2012
DOI: 10.1371/journal.pone.0038567
|View full text |Cite
|
Sign up to set email alerts
|

Novel Structurally Designed Vaccine for S. aureus α-Hemolysin: Protection against Bacteremia and Pneumonia

Abstract: Staphylococcus aureus (S. aureus) is a human pathogen associated with skin and soft tissue infections (SSTI) and life threatening sepsis and pneumonia. Efforts to develop effective vaccines against S. aureus have been largely unsuccessful, in part due to the variety of virulence factors produced by this organism. S. aureus alpha-hemolysin (Hla) is a pore-forming toxin expressed by most S. aureus strains and reported to play a key role in the pathogenesis of SSTI and pneumonia. Here we report a novel recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 35 publications
1
89
0
1
Order By: Relevance
“…Results for antigenic properties of tested PLC especially for induction of IgG antibodies after 2 weeks was consistent with those reported for P. aeruginosa PLC in mice model of Preston et al (1991). Also Adhikari et al (2012) reported that vaccinated mice showed higher ELISA and neutralizining antibody titer, this finding was consistent with the ability of antibodies to neutralize Staphylococcus aureus hemolysin (HLa) via inhibition of Hla oligomerization . On the other hand the lowering in titer of anti-PLC antibodies during the circulating time after 2 weeks assumed that these antibodies became incapable of neutralizing fresh or detoxified PLC activity in situ and don't affect the enzymatic function.…”
Section: In Vivo Immunological Characteristics and Cytotoxicity Of Psupporting
confidence: 72%
“…Results for antigenic properties of tested PLC especially for induction of IgG antibodies after 2 weeks was consistent with those reported for P. aeruginosa PLC in mice model of Preston et al (1991). Also Adhikari et al (2012) reported that vaccinated mice showed higher ELISA and neutralizining antibody titer, this finding was consistent with the ability of antibodies to neutralize Staphylococcus aureus hemolysin (HLa) via inhibition of Hla oligomerization . On the other hand the lowering in titer of anti-PLC antibodies during the circulating time after 2 weeks assumed that these antibodies became incapable of neutralizing fresh or detoxified PLC activity in situ and don't affect the enzymatic function.…”
Section: In Vivo Immunological Characteristics and Cytotoxicity Of Psupporting
confidence: 72%
“…The assay was designed based on one described by Adhikari et al (22). Briefly, serial dilutions of mouse serum were preincubated with 20 ng Hla (List Biological Laboratories, Campbell, CA) for 30 min at 37°C in 100 l total volume of PBS supplemented with 2.5% fetal bovine serum (Gibco, Life Technologies, Grand Island, NY) in a 96-well plate (MaxiSorp; Thermo Fisher, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…These toxins are lytic to host immune effector cells, are important for disease pathogenesis, and have been identified as putative vaccine targets (9)(10)(11). LukAB (12), also known as LukGH (13), is a recently described bicomponent leukotoxin that promotes S. aureus pathogenesis in both ex vivo and in vivo models of disease (7,8,12).…”
mentioning
confidence: 99%